The Impact of Stock Market Development on Economic Growth a Case of Malaysia - KHAIRUNNISA ZULKIFLI; Safian, Sharulshahida Shakrein; MOHD RADZIL, RAZIDA HANEM; SHAHARUDDIN, NORHASIMAH (Information Management and Business Review, 2024)
The stock market is important among many financial markets. Stock Market Development is one of the enabling factors for Economic Growth. The recession crisis occurred a few times and badly affected Malaysia’s Economic Growth (GDP) and Stock Market Development (SMD). Also, during the recent pandemic of COVID-19, there was a different reaction by investors and individuals overall towards the economy in Malaysia. There were inconsistent trends when the global recession in 2008 happened and COVID-19 started to spread in Malaysia for both SMD and GDP. This study aims to determine the relationship between SMD and GDP in Malaysia. Using Market Capitalization (MCAP) (as a proxy to (SMD)), Exchange Rate (EXC) and Trade Openness (TRADE) as independent variables and GDP as the dependent variable. Data from 1981 to 2020 is analyzed using Granger causality, and the ARDL method along with applying the Endogenous Growth theory. The findings of the ARDL long-run test suggested that SMD and TRADE have a positive and statistically insignificant relationship with GDP. EXC has a negative and statistically significant relationship with GDP. Granger causality test suggested a bidirectional relationship between EXC and TRADE with GDP. There is a unidirectional causality between SMD and GDP where GDP Granger causes SMD. To improve market regulation, The government should ensure the stock market is well-regulated and transparent, boost investor confidence, and increase market investment. Encouraging trade openness and exports can also help increase exchange rates and boost ringgit’s demand.